Longetudinal modeling of motor coordination levels of children aged six to 10 years of age from the Autonomous Region of Azores, Portugal - Deus, Renata Karine Batista Coelho de; Bustamante, Alcibíades; Lopes, Vitor Pires; Seabra, André Teixeira e; Silva, Rui Manuel Garganta da; Maia, José António Ribeiro (Brazilian journal of physical education and sport, 2010)
This study aims at: 1) describing models for developmental changes and interindividual differences in gross motor coordination (CoM); 2) verify the presence of gender effects; 3) and test the importance of BMI and physical activity level in motor coordination (CoM) development. Sample size comprises 285 children (143 boys and 142 girls). Motor coordination was evaluated with the test battery "Körperkoordinationstest für Kinder" (KTK) consisting of four tests: backward balance (ER), jumping sideways (SL), hopping on one leg (SM), and shifting platforms (TL). Godin and Shephard's questionnaire was used to evaluate children's physical activity level. Basic statistics were computed in SPSS. Intraindividual changes and interindividual differences were estimated within the framework of multilevel modeling using the HLM software, version 6. Mean significant changes were noticed on both genders in CoM, BMI and physical activity. Best CoM values were found for children in the 1st quartile of BMI and 3rd quartile of physical activity. These results call for a closer attention to novel approaches of didactical issues in the preparation of physical education classes, so that all children may achieve adequate levels of success according to their age